Light cement-free bonding Al2O3-SiC-C castable and preparation method thereof

By adopting a cementless bonding system in Al2O3-SiC-C refractory castable, micropores and pores are formed using silicon sol and water, and large pores are formed by combining spherical asphalt and foaming agent, the problem of liquefaction of aluminate cement at high temperatures in the prior art is solved, the thermal shock resistance and thermal insulation effect are improved, the service life is extended and the cost is reduced.

CN119638386AInactive Publication Date: 2025-03-18LUOYANG SHENG TIE REFRACTORY MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510180033.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Al2O3-SiC-C refractory castable material is converted into liquid phase due to aluminate cement at high temperatures, which weakens the anti-shrinkage ability, reduces service life, and has a high thermal conductivity to accelerate the cooling of molten iron, affecting iron production.

Method used

A cementless bonding system is adopted, and the introduction of silicon sol and water simultaneously forms micropores and pores, increasing the porosity to absorb high-temperature thermal stress, and large-size pores are formed through spherical asphalt and foaming agent, combining silicon sol to enhance the aggregate-matrix interface binding force.

Benefits of technology

The thermal shock resistance and thermal insulation effect of Al2O3-SiC-C refractory castable is improved, which extends service life, reduces blast furnace maintenance costs, and reduces iron pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a light cement-free bonding Al2O3-SiC-C castable and a preparation method thereof, and belongs to the technical field of refractory materials, brown fused alumina aggregate, silicon carbide, spherical asphalt, alpha-Al2O3 fine powder, mullite fine powder, silica sol, boron carbide and coke are used as raw materials, a water reducing agent, water, a foaming agent and a foam stabilizer are added as additives, the materials are mixed in a stirrer, and the mixture is put into a mold for molding, so that the light cement-free bonding Al2O3-SiC-C castable is obtained. The preparation method comprises the following steps: stirring, pouring and molding, curing at room temperature, demolding, drying for 24-36 hours, carrying out heat treatment at 1500-1600 DEG C in a carbon-buried atmosphere, and carrying out heat preservation for 1-3 hours to obtain the castable. The silica sol is used for replacing calcium aluminate cement to serve as a binding agent, the porosity is increased, high-temperature thermal stress is absorbed, a liquid phase generated at the high temperature is reduced, the service performance is improved, and the prepared light refractory castable can achieve the effects of reducing the mass and improving the thermal shock resistance and heat insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a lightweight cement-free Al2O3-SiC-C castable and a preparation method thereof. Background Art

[0002] In recent years, lightweight refractory materials that can be directly used for working linings have become a research focus. Lightweight refractory materials can significantly reduce the heat loss of the working lining, thereby reducing production energy consumption and achieving energy conservation and emission reduction.

[0003] For example: Chinese patent application number: 202410177575.4, the invention name is: lightweight periclase-magnesium aluminum spinel-carbon refractory material and its preparation method. The application uses 20-25wt% of the microporous periclase-magnesium aluminum spinel refractory aggregate I, 18-23wt% of the microporous periclase-magnesium aluminum spinel refractory aggregate II and 15-22wt% of the microporous periclase-magnesium aluminum spinel refractory aggregate III as the total aggregate, 31-45wt% of magnesia fine powder, 0.1-1.5wt% of elemental silicon powder and 0.5-3.5wt% of flake graphite powder as the total matrix to prepare a lightweight refractory material with low thermal conductivity, excellent thermal shock stability, good erosion resistance and other characteristics.

[0004] For example: Chinese patent application number: 202410177575.4, the name of the invention is: A method for preparing nano calcium feldspar porous refractory heat-insulating ceramic materials by foaming method. The application uses silicon dioxide powder (quartz sand fine powder), nano CaCO3, Al(OH)3 as raw materials, Al2O3 30.0-40.9wt%, SiO2 39.9-49.9wt%, CaO 10.1-25.1wt%, the total content of which is 100wt%, and adds 1.0-10.0% foaming agent, 40-70% drinking water, and 0.5-8.0% foam stabilizer to prepare calcium feldspar porous refractory heat-insulating bricks with low thermal conductivity and long life.

[0005] From the above research results, it can be seen that the preparation of lightweight refractory castables can help improve the service performance of refractory castables, reduce energy consumption in the production process, and reduce production costs.

[0006] With the technological progress of the steel industry, blast furnaces, as an important part of ironmaking technology, have higher and higher requirements on the service performance of blast furnaces. Modern ironmaking industry not only requires the refractory materials used to have high high temperature stability, excellent corrosion resistance and excellent erosion resistance, but also requires reducing iron pollution, reducing energy consumption and improving thermal efficiency.

[0007] The Al2O3-SiC-C refractory castable in the prior art has excellent high temperature performance and can resist the scouring of refractory materials by slag during service. However, the bonding system of conventional Al2O3-SiC-C refractory castable is aluminate cement bonding, which is easily converted into liquid phase at high temperature, weakening the anti-scouring ability of Al2O3-SiC-C refractory castable, reducing service life and increasing blast furnace maintenance costs. In addition, although the carbon-containing material in the Al2O3-SiC-C refractory castable has good high temperature performance and anti-scouring performance, its high thermal conductivity will accelerate the cooling rate of molten iron, which has an adverse effect on iron production. Summary of the invention

[0008] The purpose of the present invention is to provide a lightweight cement-free Al2O3-SiC-C castable and a preparation method thereof in order to solve the above problems.

[0009] The present invention achieves the above-mentioned purpose through the following technical solutions: A lightweight cement-free Al2O3-SiC-C castable is prepared from 60.0wt%-70.0wt% of brown corundum aggregate, 10.0wt%-20.0wt% of silicon carbide, 1.0wt%-4.0wt% of spherical asphalt, 10.0wt%-15.0wt% of alpha-Al2O3 fine powder, 1.0wt%-5.0wt% of mullite fine powder, 4.0wt%-7.0wt% of silica sol, 1.0wt%-3.0wt% of boron carbide, and 1.0wt%-3.0wt% of coke as raw materials, and 0.4wt%-0.6wt% of a water reducer, 7.0wt%-10.0wt% of water, 0.1wt%-0.3wt% of a foaming agent, and 1.0wt%-2.0wt% of a foam stabilizer as admixtures.

[0010] The brown corundum aggregate is made of 20.0wt%-40.0wt% 8mm-5mm brown corundum aggregate, 10.0wt%-30.0wt% 5mm-3mm brown corundum aggregate, 10.0wt%-30.0wt% 3mm-1mm brown corundum aggregate, and 30.0wt%-50.0wt% 1mm-0.088mm brown corundum aggregate.

[0011] Among them, silicon carbide uses 10.0wt%-20.0wt% of 3mm-1mm silicon carbide, 30.0wt%-50.0wt% of 1mm-0.088mm silicon carbide, and 30.0wt%-50.0wt% of silicon carbide less than 0.088mm as raw materials.

[0012] Among them, the fixed carbon content in coke is ≥83%.

[0013] Among them, the Al2O3 content in mullite fine powder is 50.0%-60.0%, and the density is ≤2.80g / cm 3 .

[0014] Among them, the foaming agent includes but is not limited to sodium lauryl sulfate, sodium polyoxyethylene fatty alcohol ether sulfate or pulp waste liquid.

[0015] The water reducing agent includes but is not limited to sodium tripolyphosphate or sodium hexametaphosphate.

[0016] Among them, the silicon oxide content in the silica sol is 30.0%-35.0%.

[0017] The present invention also provides a method for preparing a lightweight cement-free Al2O3-SiC-C castable, comprising the steps of mixing brown corundum aggregate, silicon carbide, spherical asphalt, α-Al2O3 fine powder, mullite fine powder, silica sol, boron carbide, coke, water reducer, water, foaming agent and foam stabilizer in a mixer, stirring and casting to form the mixture, performing room temperature curing and then demoulding the mixture, performing heat treatment in a carbon-buried atmosphere after drying for 24 to 36 hours at a temperature of 1500 to 1600°C, and maintaining the mixture for 1 to 3 hours to obtain the lightweight cement-free Al2O3-SiC-C castable for an iron ditch.

[0018] Among them, the volume density of Al2O3-SiC-C refractory castable after heat treatment is 2.38 / cm 3 -2.50g / cm 3 The apparent porosity is 25.0%-30.0%, the thermal conductivity is 4.8W / (m·K)-5.5W / (m·K) at 1000℃, the flexural strength is 20MPa-25MPa, and the flexural strength retention rate after three wind-cooled thermal shock tests is 77%-85%.

[0019] The advantages of the present invention are as follows: The lightweight Al2O3-SiC-C refractory castable proposed in the present invention increases micropores generated by evaporation of water during the drying process and the heat treatment process by introducing water and silica sol at the same time; larger pores are formed inside the lightweight Al2O3-SiC-C refractory castable by introducing a foaming agent, and these two parts of pores together constitute pores of two aperture sizes, which help the Al2O3-SiC-C refractory castable to absorb thermal stress at high temperature and improve thermal shock resistance; the introduction of silica sol, on the one hand, forms a silicon-containing bonding phase at the aggregate-matrix interface through the action of nano-scale silicon oxide particles, strengthens the interface bonding between the aggregate and the matrix, and further improves the erosion resistance of the Al2O3-SiC-C refractory castable; on the other hand, it helps to adhere to the surface of the pores formed by the foaming agent, increase the strength of the pore wall, and reduce the strength drop caused by the increase in porosity. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.

[0021] Example 1 The present invention relates to a lightweight cement-free Al2O3-SiC-C castable and a preparation method thereof, and the technical scheme thereof is: 60.0wt% brown corundum aggregate, 15.0wt% silicon carbide, 2.0wt% spherical asphalt, 10.0wt% α-Al2O3 fine powder, 5.0wt% mullite fine powder, 5.0wt% silica sol, 1.0wt% boron carbide, 2.0wt% coke are used as raw materials; 0.4wt% water reducer, 9.0wt% water, 0.1wt% foaming agent, and 1.0wt% foam stabilizer are added as admixtures. The above materials are mixed in a mixer for 5 minutes, stirred for 6 minutes, and then cast into shape. After curing at room temperature for 24 hours, the mold is removed, and after drying at 110°C for 24 hours, heat treatment is carried out in a carbon-buried atmosphere at a heat treatment temperature of 1550°C. After keeping warm for 1 hour, a lightweight cement-free Al2O3-SiC-C castable for iron ditch is obtained.

[0022] Among them, 8mm-5mm brown corundum aggregate accounts for 40.0wt%, 5mm-3mm brown corundum aggregate accounts for 10.0wt%, 3mm-1mm brown corundum aggregate accounts for 10.0wt%, and 1mm-0.088mm brown corundum aggregate accounts for 40.0wt%.

[0023] Among them, 3mm-1mm silicon carbide accounts for 10.0wt%, 1mm-0.088mm silicon carbide accounts for 50.0wt%, and silicon carbide less than 0.088mm accounts for 40.0wt%.

[0024] Among them, the fixed carbon content in coke is ≥83%.

[0025] Among them, the Al2O3 content in mullite fine powder is 55.0%, and the density is ≤2.80g / cm 3 .

[0026] Wherein, the foaming agent is sodium lauryl sulfate.

[0027] Among them, the water reducing agent is sodium tripolyphosphate.

[0028] Among them, the silicon oxide content in the silica sol is 30.0%.

[0029] After testing, the bulk density of the Al2O3-SiC-C refractory castable after heat treatment is 2.44g / cm 3The apparent porosity is 26.3%, the thermal conductivity is 5.2W / (m·K) at 1000℃, the flexural strength is 21.4MPa, and the flexural strength retention rate after three wind-cooled thermal shock tests is 80%.

[0030] Example 2 The present invention relates to a lightweight cement-free Al2O3-SiC-C castable and a preparation method thereof, and the technical scheme thereof is: 65.0wt% brown corundum aggregate, 10.0wt% silicon carbide, 1.0wt% spherical asphalt, 10.0wt% α-Al2O3 fine powder, 4.0wt% mullite fine powder, 4.0wt% silica sol, 3.0wt% boron carbide, 3.0wt% coke are used as raw materials; 0.6wt% water reducer, 7.0wt% water, 0.2wt% foaming agent, 2.0wt% foam stabilizer are added as admixtures. The above materials are mixed in a mixer for 5 minutes, stirred for 7 minutes and cast into shape, demolded after curing at room temperature for 30 hours, dried at 100℃ for 24 hours and then heat treated in a carbon atmosphere at a heat treatment temperature of 1500℃. After keeping warm for 2 hours, a lightweight cement-free Al2O3-SiC-C castable for iron ditch is obtained.

[0031] Among them, 8mm-5mm brown corundum aggregate accounts for 30.0wt%, 5mm-3mm brown corundum aggregate accounts for 20.0wt%, 3mm-1mm brown corundum aggregate accounts for 20.0wt%, and 1mm-0.088mm brown corundum aggregate accounts for 30.0wt%.

[0032] Among them, 3mm-1mm silicon carbide accounts for 20.0wt%, 1mm-0.088mm silicon carbide accounts for 40.0wt%, and silicon carbide less than 0.088mm accounts for 40.0wt%.

[0033] Among them, the fixed carbon content in coke is ≥86%.

[0034] Among them, the Al2O3 content in mullite fine powder is 60.0%, and the density is ≤2.80g / cm 3 .

[0035] Wherein, the foaming agent is sodium sulfate of fatty alcohol polyoxyethylene ether.

[0036] Among them, the water reducing agent is sodium tripolyphosphate.

[0037] Among them, the silicon oxide content in the silica sol is 35.0%.

[0038] After testing, the bulk density of Al2O3-SiC-C refractory castable after heat treatment is 2.40g / cm 3The apparent porosity is 28.0%, the thermal conductivity is 5.0W / (m·K) at 1000℃, the flexural strength is 23.4MPa, and the flexural strength retention rate after three wind-cooled thermal shock tests is 82%.

[0039] Example 3 The present invention relates to a lightweight cement-free Al2O3-SiC-C castable and a preparation method thereof, and the technical scheme thereof is: 70.0wt% brown corundum aggregate, 10.0wt% silicon carbide, 2.0wt% spherical asphalt, 10.0wt% α-Al2O3 fine powder, 1.0wt% mullite fine powder, 4.0wt% silica sol, 1.0wt% boron carbide, 2.0wt% coke are used as raw materials; 0.4wt% water reducer, 10.0wt% water, 0.3wt% foaming agent, and 1.0wt% foam stabilizer are added as admixtures. The above materials are mixed in a mixer for 4 minutes, stirred for 6 minutes, and then cast into shape. After curing at room temperature for 36 hours, they are demoulded, dried at 120℃ for 36 hours, and then heat treated in a carbon-buried atmosphere at a heat treatment temperature of 1600℃. After heat preservation for 3 hours, a lightweight cement-free Al2O3-SiC-C castable for iron ditch is obtained.

[0040] Among them, 8mm-5mm brown corundum aggregate accounts for 20.0wt%, 5mm-3mm brown corundum aggregate accounts for 30.0wt%, 3mm-1mm brown corundum aggregate accounts for 20.0wt%, and 1mm-0.088mm brown corundum aggregate accounts for 30.0wt%.

[0041] Among them, 3mm-1mm silicon carbide accounts for 10.0wt%, 1mm-0.088mm silicon carbide accounts for 40.0wt%, and silicon carbide less than 0.088mm accounts for 50.0wt%.

[0042] Among them, the fixed carbon content in coke is ≥84%.

[0043] Among them, the Al2O3 content in mullite fine powder is 50.0%, and the density is ≤2.80g / cm 3 .

[0044] Wherein, the foaming agent is pulp waste liquid.

[0045] Among them, the water reducing agent is sodium hexametaphosphate.

[0046] Among them, the silicon oxide content in the silica sol is 30.0%.

[0047] After testing, the bulk density of the Al2O3-SiC-C refractory castable after heat treatment is 2.48g / cm 3The apparent porosity is 25.4%, the thermal conductivity is 5.4W / (m·K) at 1000℃, the flexural strength is 24.8MPa, and the flexural strength retention rate after three wind-cooled thermal shock tests is 84%.

[0048] By adopting the above technical solution, the present invention has the following positive effects compared with the prior art: The present invention uses silica sol instead of calcium aluminate cement as a binder, which helps to increase the porosity and absorb high-temperature thermal stress, and reduces the liquid phase generated at high temperature, thereby improving service performance.

[0049] The lightweight Al2O3-SiC-C refractory castable prepared by the invention can reduce the weight and improve the thermal shock resistance and heat insulation effects.

[0050] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A lightweight cement-free Al2O3-SiC-C castable, characterized by: The method comprises 60.0wt%-70.0wt% of brown corundum aggregate, 10.0wt%-20.0wt% of silicon carbide, 1.0wt%-4.0wt% of spherical asphalt, 10.0wt%-15.0wt% of α-Al2O3 fine powder, 1.0wt%-5.0wt% of mullite fine powder, 4.0wt%-7.0wt% of silica sol, 1.0wt%-3.0wt% of boron carbide and 1.0wt%-3.0wt% of coke as raw materials, and 0.4wt%-0.6wt% of a water reducer, 7.0wt%-10.0wt% of water, 0.1wt%-0.3wt% of a foaming agent and 1.0wt%-2.0wt% of a foam stabilizer as admixtures.

2. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The brown corundum aggregate is made of 20.0wt%-40.0wt% of 8mm-5mm brown corundum aggregate, 10.0wt%-30.0wt% of 5mm-3mm brown corundum aggregate, 10.0wt%-30.0wt% of 3mm-1mm brown corundum aggregate, and 30.0wt%-50.0wt% of 1mm-0.088mm brown corundum aggregate.

3. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The silicon carbide is made of 10.0wt%-20.0wt% of 3mm-1mm silicon carbide, 30.0wt%-50.0wt% of 1mm-0.088mm silicon carbide, and 30.0wt%-50.0wt% of silicon carbide less than 0.088mm.

4. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The fixed carbon content in the coke is ≥83%.

5. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The Al2O3 content of the mullite fine powder is 50.0%-60.0%, and the density is ≤2.80g / cm 3 .

6. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The foaming agent includes but is not limited to sodium lauryl sulfate, sodium polyoxyethylene fatty alcohol ether sulfate or pulp waste liquid.

7. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The water reducing agent includes but is not limited to sodium tripolyphosphate or sodium hexametaphosphate.

8. A lightweight cement-free Al2O3-SiC-C castable according to claim 1, characterized in that: The silicon oxide content in the silica sol is 30.0%-35.0%.

9. A method for preparing a lightweight cement-free Al2O3-SiC-C castable according to any one of claims 1 to 8, characterized in that: Brown corundum aggregate, silicon carbide, spherical asphalt, α-Al2O3 fine powder, mullite fine powder, silica sol, boron carbide, coke, water reducer, water, foaming agent and foam stabilizer are mixed in a mixer, stirred and cast into shape, demolded after room temperature curing, and heat treated in a carbon-buried atmosphere at a temperature of 1500°C to 1600°C after drying for 24 to 36 hours. After keeping warm for 1 to 3 hours, a lightweight cement-free Al2O3-SiC-C castable for iron ditch is obtained.

10. The method for preparing a lightweight cement-free Al2O3-SiC-C castable according to claim 9, characterized in that: The bulk density of Al2O3-SiC-C refractory castable after heat treatment is 2.38 / cm 3 -2.50g / cm 3 The apparent porosity is 25.0%-30.0%, the thermal conductivity is 4.8W / (m·K)-5.5W / (m·K) at 1000℃, the flexural strength is 20MPa-25MPa, and the flexural strength retention rate after three wind-cooled thermal shock tests is 77%-85%.

Citation Information

Patent Citations

  • Lightweight periclase-magnesium aluminate spinel-carbon refractory material and preparation method thereof

    CN118125841A

  • Iron-runner quick-drying casting material combined with silica sol

    CN101941845A

  • Al2O3-SiC-C iron runner casting material and preparation method thereof

    CN103011868A

  • Magnesium aluminate spinel light refractory castable and production method thereof

    CN103011885A

  • High-oxidation-resistance non-cement bonded Al2O3-SiC-C refractory castable and preparation method thereof

    CN112608138A